2017
DOI: 10.1073/pnas.1706016114
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism correlates with metabolic similarity in diverse bacteria

Abstract: In the , Charles R. Darwin [Darwin C (1859)] proposed that the struggle for existence must be most intense among closely related species by means of their functional similarity. It has been hypothesized that this similarity, which results in resource competition, is the driver of the evolution of antagonism among bacteria. Consequently, antagonism should mostly be prevalent among phylogenetically and metabolically similar species. We tested the hypothesis by screening for antagonism among all possible pairwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
129
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 35 publications
12
129
2
Order By: Relevance
“…By measuring interactions across many environments, our study produced many instances in which at least one of the two cocultured strains grew poorly or not at all, a regime in which we found positive interactions were far more likely to occur than previously measured. The study also produced instances where both strains grew well and antagonism was common, a result consistent with previous large-scale studies of bacterial interactions (37,38).…”
Section: Discussionsupporting
confidence: 85%
“…By measuring interactions across many environments, our study produced many instances in which at least one of the two cocultured strains grew poorly or not at all, a regime in which we found positive interactions were far more likely to occur than previously measured. The study also produced instances where both strains grew well and antagonism was common, a result consistent with previous large-scale studies of bacterial interactions (37,38).…”
Section: Discussionsupporting
confidence: 85%
“…In support of this idea, competition by interference among pairs of 148 soil Proteobacteria, Actinobacteria, Bacteroidetes and Firmicutes revealed that antagonism increases with phylogenetic proximity (Russel, Roder, Madsen, Burmolle, & Sorensen, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Competitive exclusion through niche similarities tends to limit the functional (and phylogenetic) similarity of competing lineages, thus favouring the co‐existence of distantly related taxa (Webb et al, ). In support of this idea, competition by interference among pairs of 148 soil Proteobacteria, Actinobacteria, Bacteroidetes and Firmicutes revealed that antagonism increases with phylogenetic proximity (Russel, Roder, Madsen, Burmolle, & Sorensen, ). In contrast, relative fitness differences associated with particular superior clades tend to outcompete entire distant lineages resulting in the co‐existence of closely related taxa (Mayfield & Levine, ).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, plasmids may be more strongly challenged by other intracellular plasmid-like elements which, while not being especially detrimental to the host, may compete directly for common cellular resources 42,43 . The latter argument receives support from the accepted community ecology view that similar entities compete more strongly for overlapping niches and resources 44,45,46 .…”
Section: Discussionmentioning
confidence: 98%